Diagnostic approach in children with unusual symptoms of acquired hypothyroidism. When to look for pituitary hyperplasia? - Mirjana Kocova; Nikolina Zdraveska; Rozana Kacarska; Elena Kochova (Walter de Gruyter GmbH, 2016)
Pituitary hyperplasia secondary to primary longstanding hypothyroidism has been reported in the literature in adults and rarely in children.